Concreto autoadensável com agregados graúdos reciclados de concreto - Moreira, Kelvya Maria de Vasconcelos (2012)
The self-compacting concrete (SCC) has intrinsic properties that distinguish it known current conventional concrete. It is factors like self - compacting capacity, high amount of fines and mandatory use of superplasticizer that make the SCC a material of high performance, favorable to the durability and is considered an evolution in concrete technology and prone to become the future conventional concrete. On the other hand, the residue originated in the construction industry itself has aroused serious concern to the community, because it is a residue difficult to discard . It is generated in ever - increasing volumes due to economic growth in the country with con sequent increase in power population's purchasing. From this perspective , we analyzed the production of SCC with replacemen t of natural coarse aggregate (NCA) for recycled aggregates from concrete recycling, called recycled coarse aggregate (RCA), in the percentages of 0%, 10%, 20% and 30%. Knowing that recycled aggregate, in general, has distinct characteristics of natural aggregate, the methodology started with the treatment of RCA and physical characterization of all aggregates (conventional and recycled). Then, it was done the dosage study with the w/c ratio of 0.35, 0.45 and 0.55. After, we studied a total of 12 mixtures of SCC to evaluate its properties in fresh and hardened state. The tests in the hardened state were: compressive strength at 28 and 56 days, modulus of elasticity at 56 days, water absorption by immersion at 28 days, content of voids a t 28 days, specific gravity at 28 days and the depth of natural carbonation at 200 days. We proceeded to statistical processing of results by analysis of v ariance (ANOVA) followed by mathematical modeling and model‟s ANOVA . Finally, it was concluded that the high content of superplasticizer results from the dosage study of lower w/c ratio can be influenced to achieve concretes more workable and less sensitiv e to the incorporation of an aggregate more porous than the natural aggregate. It was also found that the properties of the SCC manufactured were affected more significantly by the w/c ratio, indicating the possibility of substitution of higher levels of NCA by RCA